DAMPAK ADAPTASI MEDIA SOSIAL DALAM LINTAS BUDAYA DAN PERTAHANAN AKULTURASI BUDAYA PADA GENERASI Z - Irma Tangkelangan; Yusmiar Br Tarigan; Nasrani Wuner; Mint Husen R. Aditama (JUPE : Jurnal Pendidikan Mandala, 2022)
The purpose of this study is to find out how the Impact of Social Media Adaptation in Cross Culture and Defense of Cultural Acculturation in Generation Z In the Minahasa Tomohon Community, North Sulawesi. Many generation Z who were born in the 1995-2010 range were affected by the use of smartphones to access the latest news and did not pay attention to existing local culture. This influence is great for the threat of cultural literacy that is transmitted from gene X to generation Z. This type of research is case study research using qualitative methods with an interpretive phenomenological approach. The informants in this study were representatives of Manado University students who live around the Tomohon area using purposive sampling. Data collection techniques namely observation, interviews and documentation were carried out to find out how the Impact of Social Media Adaptation in Cross Culture and Defense of Cultural Acculturation in Generation Z. The results of the study concluded that social media has had a cultural shifting effect on generation z in Tomohon, especially in terms of dress, language and behavior.Â